The Importance of Local Aspects in Traditional Industries' Competitiveness: an Overview of the State of the Art - Juan Ignacio Dalmau-Porta; Maria del Val Segarra-O\~na; José Luis Hervás- Oliver (European Regional Science Association (ERSA), 2003)
The process of globalization of the economy has modified the productive activity, enlarging the level of rivalry among firms. If it wants to respond with success to this new situation, a high competitiveness level should be maintained. The word is to the order of the day, with an implicit meaning of progress and advance, although it is not easy to find a definition of it. Many authors have tried this theme in depth. As Pérez (2001) indicates, there are four factors that determine the success of a business: the region where it is located, the industry to which it belongs, the cluster, and its own resources. According to other authors, the succes or failure of a business will be determined by the resources, the capacities and the strategies applied. There are many authors that affirm that competitiveness is a very located process, based on aglomerations of firms organized around one or various related industries, that converge. (Porter, 1985, 1998, Grant, 1996b, Mintzberg 1999). Some other affirm that the strategy of the firms must be based on internal resources, having these the main importance upon the market (Grant, 1996b). According to Grant (1996b), it is more advisable for the businesses that they become competitive based on its endogenous factors. The capacity of reaction of a firm requires not only a deep knowledge of the environment, but it also depends on the function of management, and the degree in which the culture of the organization affects the profit of value and the obtention of benefits of the business. Although these two theories, the external one the internal one have been presented like different alternatives for the study of an industry, other authors consider them complementary (Henderson, 2000), since, while the first one focuses its attention on the structure of the industry, the second does it in the fact that the capabilities (abilities, investments, knowledge, etc.) developed by an organization are the ones that build an strong competitive advantage. The study has focused on the macroeconomic focus, distinguishing also the internal and external aspects of it. Some of the most accepted models by the scientific comunity are presented within the external focus. The analysis of the geographical variable as base of a sinergic action of the businesses and of the related agencies established in an specific surroundings, the cluster, has been considered as part and development of the competitive strategy Finally both theries have been opposed and a new theoretical model, based on the adaptation of the main two currents that currently exist, has been proposed.
Keywords: 330